Knowledge, Attitude and Exposure to Secondhand Smoking Among Women in Rural Setting - Chowdhury, Ayesha Mahzabin; Lima, Fatema Akter; Alam, Md Hasibul; Chowdhury, Nafisa Marzan; Pervin, Shanaz; Hossain, Md Anwar (Central Medical College Journal, 2024)
Background: Secondhand smoking (SHS) is a major public health problem of our country because the people of Bangladesh are highly exposed to it due to high prevalence of smoking. Objective: To assess the knowledge, attitude and exposure to secondhand smoking among women in rural setting. Methods: The cross- sectional study is conducted over 3 months (September 2022 to November 2022) among 383 women of reproductive age (15-49) in Uttar Rampur village under Sadar South Upazilla in Cumilla district. Women having any physical & psychological disorder are excluded. Participants are selected by convenient sampling technique; data are collected by face to face interviewing with a semi-structured questionnaire to assess socio-demographic characteristics, knowledge, attitude and exposure to secondhand smoking. Data are analyzed by SPSS software. Results: In this study, the mean age of the participants is31.57±7.582 where majority (44.1%) of the participants are in the age group 25-34 years; most of them are Muslims (95.6%) and housewives(87.2%) and 27.2% has secondary education. Regarding knowledge about SHS, majority (67.6%) of the participants are aware of SHS. Among them 37.6% recognize marketplace as a source of SHS and 29.5% tell lung disease as health consequence of SHS. About attitude towards SHS, almost all (98.5%) the participants support that smoking should be completely banned in all places, 88.4% tell about right to ask other people not to smoke, 87.3% tell about presence of SHS encourages young peopleto begin to smoke and 79.2% tell about allowing SHS athome discourages smoking from quitting. Regarding exposure to SHS, most of them are exposed (95.0%) and 46.7% are exposed daily. 53.6% are exposed from husband and manufactured tobacco is widely exposed type (69.5%). Conclusion: Awareness should be raised through national wide educational program to reduce exposure to secondhand smoke and enhancement of self-efficiency to avoid secondhand smoking. Central Medical College Journal Vol 7 No 1 January 2023 Page: 26-31